Constraints on mantle source and interactions from He-Sr isotope variation in Italian Plio-Quaternary volcanism. - NUCCIO, Pasquale; STUART FM; DI LIBERTO V; ELLAM RM (Geochemistry, Geophysics, Geosystems, 2008)
[1] Helium isotope ratios of olivine and pyroxene phenocrysts from Plio-Quaternary volcanic rocks from southern Italy (seven Aeolian Islands, Mt. Vulture, Etna, Ustica, and Pantelleria) range from 2.3 to 7.1 Ra. Importantly, the phenocryst 3He/4He correlate well with whole rock Sr isotopic composition (0.70309– 0.70711), reflecting the mixing of two sources. A significant contribution of He from crustal contamination is recorded only occasionally (e.g., pyroxenes from Vulcano). When merged with data from the Roman Comagmatic Province, a remarkably strong near-linear He-Sr isotope correlation is apparent. The general northward decrease in 3He/4He corresponds to an increase in 87Sr/86Sr (and a decrease in 143Nd/144Nd and 206Pb/204Pb) that is due to increasing metasomatic enrichment of the mantle wedge via subduction of the Ionian-Adriatic plate. Calculations based on the ingrowth of 4He in the wedge and on the 4He content of the subducting crust show that mechanisms of enrichment in radiogenic He are effective only if the wedge is strongly depleted in He relative to best estimates of the depleted mantle. This can be accommodated if the process of metasomatism by the subduction fluids depletes the mantle wedge. The 3He/4He of Pantelleria, Etna, Iblei, Ustica, Alicudi, and Filicudi basalts (7.0 ± 0.6 Ra) define the mantle composition least affected by subduction-related metasomatism. Although these volcanoes are from a variety of tectonic regimes (subduction-related, intraplate, rifting), their similarities suggest a common origin of geochemical features. Their characteristics are consistent with a HIMU-type mantle that either is younger than the Cook- Austral island end-member or has a lower 238U/204Pb. Q02001, doi:10.1029/2007GC001730 ISSN: 1525-2027 Click Here for Full Article Copyright